POLA SEBARAN DAN KONDISI MIKROHABITAT RAMA-RAMA (Thalassina spp.) DI LINGKUNGAN PESISIR BUKIT BATU, BENGKALIS, RIAU - Ila Rahayu; Ahmad Muhammad; Windarti ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Mud lobsters (Thalassina) are one of the most common macrofauna in mangrove ecosystems, especially in the Indo-Pacific region. The presence of this fauna is typically marked by mud mounds that are hardly overseen in its habitats, as a result of its bioturbation activities. This study, which focused on Bukit Batu coastal area in Riau Province, aimed to identify the occurring species in the area, describe the distribution and abundance patterns along the sea-inland gradient, and identify critical factors affecting the patterns. Observations were carried out in the focal area from September to November 2013 along four 1100 m-long transects, on each of which 10 quadratic plots of 10 m x 10 m were established in 100-m interval. The observed parameters were the characteristics of vegetation cover, soil BD, groundwater level, groundwater salinity and pH, beside number of “active” mounds. At least two species of mud lobsters were countered, T. anomala and T. spinosa. Mud lobster mounds were totally absent at a distance of 0 and 100 m from lowest-tide line, while most abundant at a distance of 200 m, with 9.4 mounds/m2. The abundance decreased sharply following the increasing distance toward inland, which was down to 0.09 mounds/m2 at 1100 m. Mounds were more evenly distributed toward the sea, while increasingly random as their density decreased. Groundwater salinity was the most critical affecting mound distribution and abundance.